1986
DOI: 10.1090/s0025-5718-1986-0815849-1
|View full text |Cite
|
Sign up to set email alerts
|

Breeding amicable numbers in abundance

Abstract: We give some new methods for the constructive search for amicable number pairs. Our numerical experiments using these methods produced a total of 3501 new amicable pairs of a very special form. They provide some experimental evidence for the infinity of such pairs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Sometimes e 1 contained one more prime than e 2 . In this case, an amicable pair produced is of type (3,2). At first, the choices for e 1 and e 2 were often determined by looking at known pairs of other types.…”
Section: Inputs To the Programmentioning
confidence: 97%
See 1 more Smart Citation
“…Sometimes e 1 contained one more prime than e 2 . In this case, an amicable pair produced is of type (3,2). At first, the choices for e 1 and e 2 were often determined by looking at known pairs of other types.…”
Section: Inputs To the Programmentioning
confidence: 97%
“…The pair (17296, 18416) has often been attributed to Fermat, but it was actually first found in the early 14th century by Ibn al-Banna in Marakesh and also by Kamaladdin Farisi in Bagdad. The pair (9363584, 9437056) has often been attributed to Descartes, but it was actually first discovered by Muhammad Baqir Yazdi in Iran [3]. Euler found 59 more pairs by noticing that each member of a known pair had a common factor and then a product of different primes on the end.…”
Section: Introductionmentioning
confidence: 99%
“…Type (i, 1) amicable pairs have been the object of special investigation and search [1], [2], [3], [5]. Often it is possible to construct other amicable pairs from them [6].…”
mentioning
confidence: 99%
“…Often it is possible to construct other amicable pairs from them [6]. Also, until Euler's time [4], the only three known amicable pairs were of type (2,1). One of these is the smallest existing amicable pair (2 2 · 5 · 11, 2 2 · 71), which was known to the Pythagoreans.…”
mentioning
confidence: 99%
“…In [8] a substantial part of the new APs found there was constructed from such mother pairs. In [1], Borho and Hoffmann have partially generalized the methods from [8] by introducing the concept of a breeder: a breeder is a pair of positive integers (ax, a2) such that the equations ax + a2x = a(ax) = a(a2)(x + 1) In our list of 1427 APs we found a few APs, e.g., #647 and #955, which suggested that the condition gcà(a, u) = 1 in Theorem 1 may be dropped. In fact, we have It is known [5] that most even APs have a pair sum which is = 0 (mod 9).…”
mentioning
confidence: 99%